APLIKASI PEMESANAN ONLINE KARTU UNDANGAN BERBASIS WEB PADA CV. JAMBI GLOBAL PRINTING: APPLICATION: ONLINE ORDER: INVITATION: PROMOTION - Pariyadi; Ardiansyah (FORTECH (Journal of Information Technology), 2020)
CV. Jambi Global Printing is a business engaged in printing or Advertising. The company gets problems that often arise due to promotions and information submitted using brochures and invitation bookings are still manual. Manually here means the invitation order is still manual and consumers can only order invitations directly to the printing site, of course this will complicate the development of this printing press. What is a weakness is that the company has difficulty in delivering information about products that are marketed, if this happens continuously, this will have an impact on their income because it can only have a marketing scope that is not wide enough. To overcome this error, it is necessary to build a tool in the form of an online-based program, which will make it easier for consumers to get invitation information and make it easier for consumers to order invitations online. The application used in helping processing the data is web-based programming. Chosen based on the web because information can be obtained easily anywhere and anytime. The advantages of this information system are as a means of information for consumers, as a place to describe the types of invitations, in lieu of brochures for promotional events in finding consumers.